2022
DOI: 10.1017/s0021932022000359
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean delivery in Uganda: Do non-clinical factors explain the trend?

Abstract: The aim of this paper was to assess the association between non-clinical factors and Caesarean delivery in Uganda. Self-reported data from the individual recode file were extracted from the 2016 Uganda Demographic and Health Survey (UDHS), with a sub sample of 9929 women aged 15-49 with a recent birth in the last 5 years preceding the survey. Chi-square tests and multivariate comlementary log-log regression models were used to examine the relationship between non-clinical factors and Caesarean section delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…And this is higher compared to 15.7% of the Ghanaian general population (Alhassan, 2022). And this is even higher compared to results from other African countries (Adewuyi et al, 2019;Nakinobe et al, 2022;Kibe et al, 2022). However, this is low compared with results from developed countries including 25.9% in China, 32.3% in Australia/New Zealand, and 45.9% in Brazil (Betrán et al, 2016).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…And this is higher compared to 15.7% of the Ghanaian general population (Alhassan, 2022). And this is even higher compared to results from other African countries (Adewuyi et al, 2019;Nakinobe et al, 2022;Kibe et al, 2022). However, this is low compared with results from developed countries including 25.9% in China, 32.3% in Australia/New Zealand, and 45.9% in Brazil (Betrán et al, 2016).…”
Section: Discussionmentioning
confidence: 63%
“…Developed countries have high rates of CS delivery, including 25.9% in China, 32.3% in Australia/New Zealand, and 45.9% in Brazil ( Betrán et al, 2016 ). And in Africa, the prevalence differs among the countries: Uganda (7.0% in 2022), Rwanda (15.6% in 2020), and Nigeria (2.1%) ( Adewuyi et al, 2019 ; Nakinobe et al, 2022 ; Kibe et al, 2022 ). In Ghana, a recent national study by Alhassan reported the prevalence to be 15.7%, which is higher as compared to 11.4% in an earlier study by Dankwa et al ( Alhassan, 2022 ; Dankwah et al, 2019 ).…”
Section: Review Of Literaturementioning
confidence: 99%